2015
DOI: 10.1007/s00192-015-2826-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence: prevalence, pattern, and opportunistic screening in Ile-Ife, Nigeria

Abstract: Urinary incontinence was occasionally present, but usually undisclosed by women attending the general outpatient clinic, unless when specifically asked by their physicians. Opportunistic screening is therefore recommended in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
3
11
0
2
Order By: Relevance
“…Study design may also be another factor influencing the incidence rates of UI. Most of the studies were designed at outpatient clinics [3][4][5][6] and some of them had retrospective design [3] . Telephone interviews were used to collect data in some studies [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study design may also be another factor influencing the incidence rates of UI. Most of the studies were designed at outpatient clinics [3][4][5][6] and some of them had retrospective design [3] . Telephone interviews were used to collect data in some studies [2] .…”
Section: Discussionmentioning
confidence: 99%
“…The other subtypes comprised of nocturnal enuresis, postural incontinence, continuous incontinence, insensible incontinence, and coital incontinence. UI is a worldwide health problem with prevalence rates of 25-45% in most of the reported studies which increases with aging [2][3][4][5] . This variation depends on the differences among the surveys according to their design, differences between the characteristics of cohorts (age, comorbidities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when comparing this study with other studies on UI in the same geopolitical zone in Nigeria, there is a little improvement in the number of women that sought medical attention because none of the women in those studies sought for medical intervention. [13,27] Severity of the symptoms is one of the reasons identified in previous studies as why women seek out for medical attention, conversely in this study majority of the women who leaked urine did so about 8 times a week. [26,27] A higher proportion of the study participant reported symptoms of stress UI which is comparable to other studies, [6,19,27,28] however the study by Ojengbede et al reported a higher proportion (13.7%) of women with urge incontinence in the same environment.…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of UI observed in this study falls within the range of 2.8% to 38.1% reported among non -pregnant women in previous Nigerian studies. [13,18,19] However, higher rate have been documented in other countries Turkey (44.6%), France (44%), Germany (41%) United Kingdom (42%) and United states (53.4%). [6,20,21] This difference might be due to the difference in the study population, location and sample size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation